REFORMULASI KURIKULUM BERBASIS LITERASI DIGITAL PADA ERA ARTIFICIAL INTELLIGENCE: PERSPEKTIF TEKNOLOGI PENDIDIKAN - Syukron Jamal (Staisman Press, 2026)
Digital transformation and the rapid development of Artificial Intelligence (AI) have significantly changed various aspects of human life, including education systems. These changes require educational institutions to develop human resources equipped with adequate digital literacy skills to adapt to increasingly complex technological developments. However, several indicators reveal that literacy levels in Indonesia still face substantial challenges. The Programme for International Student Assessment (PISA) 2022 reported that Indonesian students’ reading literacy performance remains below the OECD average (OECD, 2023). This condition is reinforced by the Indonesian Digital Society Index (IMDI), which indicates that Indonesia's digital maturity remains at a moderate level (Ministry of Communication and Digital Affairs of the Republic of Indonesia, 2025). This article aims to analyze curriculum reformulation in strengthening digital literacy in the era of Artificial Intelligence from the perspective of educational technology. The study employs a qualitative approach using a library research method. Data were collected from OECD and UNESCO reports, scholarly journals, and educational technology theories. The findings indicate that digital literacy-based curriculum development should integrate twenty-first-century competencies, AI literacy, and educational technology theories such as constructivism, connectivism, multimedia learning, TPACK, and SAMR. Curriculum reformulation, teacher competency development, and digital infrastructure enhancement are strategic factors in creating an adaptive learning ecosystem. Therefore, digital literacy-based curriculum reform is essential to prepare learners for the challenges of Society 5.0.